Development of Novel Alkoxyisoxazoles as Sigma-1 Receptor Antagonists with Antinociceptive Efficacy - Sun, H.; Shi, M.; Zhang, W.; Zheng, Y.; Xu, Y.; Shi, J.; Liu, T.; Gunosewoyo, Hendra; Pang, T.; Gao, Z.; Yang, F.; Tang, J.; et al. (American Chemical Society, 2016)
A novel series of sigma (s) receptor ligands based on an alkoxyisoxazole scaffold has been designed and synthesized. Preliminary receptor binding assays identified highly potent (Ki < 1 nM) and selective s1 ligands devoid of binding interactions with the monoamine transporters DAT, NET, and SERT. In particular, compound 53 was shown to possess significant antinociceptive activity in the mouse formalin-induced inflammation pain model when administered intraperitoneally at 40 and 80 mg/kg. Initial pharmacokinetics evaluation indicated an excellent brain exposure following oral dosing in mice, suggesting that further investigation into the use of alkoxyisoxazoles as s1 ligands for antinociception is warranted. This study supports the notion that selective s1 antagonism could be a useful strategy in the development of novel antipain therapy.